Advances in visual informatics : 5th International Visual Informatics Conference, IVIC 2017, Bangi, Malaysia, November 28-30, 2017, Proceedings /: 5th International Visual Informatics Conference, IVIC 2017, Bangi, Malaysia, November 28-30, 2017, Proceedings. (2017) - Unknown
No abstract available